Effect of oxidation on flexural strength and thermal properties of AlN ceramics with residual stress and impedance spectroscopy analysis of defects and impurities. Issue 10 (July 2019) - Jiang, Hai; Wang, Xiao-Hong; Fan, Gui-Fen; Fu, Ming; Lei, Wen; Wang, Xiao-Chuan; Liang, Fei; Lu, Wen-Zhong
Abstract: The effect of oxidation in air on the phase composition, microstructure, flexural strength and thermal property of AlN ceramics was investigated. Oxidation was found to produce a continuous oxide layer on the surface of AlN samples. The flexural strength and thermal conductivity of AlN ceramics significantly improved after oxidation at 1000 °C and 1100 °C. Residual stress in the AlN ceramic matrix was enhanced by oxidation. The enhanced residual compressive stresses inhibited crack propagation and reduced interfacial thermal resistance, thereby improving the flexural strength and thermal conductivity of AlN ceramics. Electrochemical impedance spectroscopy was further used to analyze the defects in AlN ceramics. The increase in fitting grain resistance revealed a decrease in aluminum vacancy concentration in oxidized AlN sample, which resulted in high thermal conductivity. Therefore, oxidation at a certain temperature is pretty effective to obtain excellent performance for AlN ceramics.